Pembuatan Pestisida Alami Daun Pepaya untuk Mengendalikan Hama dan Penyakit Tumbuhan dalam Kegiatan Pengabdian Masyarakat - Anisa Risanda Damanik; Dwi Ardi Dermawan; Dahlianasari Syahputri; Siti Khadijah Nasution; Windi Ariani Pratiwi; Habib Syarkowi Harahap (Jurnal Kemitraan Masyarakat, 2025)
Padang Brahrang is a village located in the city of Binjai, Langkat Regency, which has many stories ranging from the cleanliness of the village, which has greenery and cultivation of plants ranging from flowers to vegetables. But in this case, we students of North Sumatra State Islamic University are doing Community Service activities in Padang Brahrang village, one of the activities we do is making natural pesticides from papaya leaves that are useful for keeping plants or plants from pests and diseases. . The type of research used in this paper uses qualitative research methods with descriptive approaches. Pesticide manufacturing greatly influenced the development of plants and plants in the village, resulting in the production of pesticides given to the mother and father of village devices that cultivated plants and nearby communities.